2009
DOI: 10.1152/ajpgi.90257.2008
|View full text |Cite
|
Sign up to set email alerts
|

Role of iron in the pathogenesis of cysteamine-induced duodenal ulceration in rats

Abstract: Cysteamine induces perforating duodenal ulcers in rats within 24-48 h. This reducing aminothiol generates hydrogen peroxide in the presence of transition metals (e.g., ferric iron), producing oxidative stress, which may contribute to organ-specific tissue damage. Since most intestinal iron absorption takes place in the proximal duodenum, we hypothesized that cysteamine may disrupt regulation of mucosal iron transport, and iron may facilitate cysteamine-induced duodenal ulceration. We show here that cysteamine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 67 publications
0
22
0
1
Order By: Relevance
“…This model has been considered the standard model for experimental duodenal ulcers and has been used for the biological efficacy assessment of new anti-ulcer drugs. According to Khomenko et al (2009), animals treated with cysteamine display a significant increase in duodenal lesions due to the generation of free radicals. Fig.…”
Section: Treatments (Po)mentioning
confidence: 99%
“…This model has been considered the standard model for experimental duodenal ulcers and has been used for the biological efficacy assessment of new anti-ulcer drugs. According to Khomenko et al (2009), animals treated with cysteamine display a significant increase in duodenal lesions due to the generation of free radicals. Fig.…”
Section: Treatments (Po)mentioning
confidence: 99%
“…Cysteamine hydrochloride inhibits alkaline mucus secretion from the Brunner's gland in the proximal duodenum and stimulates the rate of gastric acid secretion (Schwedes et al, 1977). According to Khomenko et al (2009) animals treated with cysteamine also display a significant increase in duodenal lesions due to the generation of free radicals. Fig.…”
Section: Tablementioning
confidence: 99%
“…Some studies have suggested that transcription factors such as hypoxia-inducible factor-1α and early growth response factor-1 and their target genes are involved in pathogenesis of cysteamine-induced ulcers [38,39]. Moreover, a recent study performed by Khomenko et al has produced strong evidence that cysteamine disrupts regulation of mucosal iron transport, leading to increased mucosal susceptibility to oxidative stress [40]. …”
Section: Introductionmentioning
confidence: 99%